(untitled) (Research, Society and Development, 2022)
The expansion of agricultural and livestock production in Brazil has led to the intensification of the use of pesticides, a worrying fact given the negative effects of these products on the environment and human health. Bahia is one of the main states that consumes pesticides and previous studies in the Bahia municipality of Crisópolis-BA have shown a wide use of these products by the population. Considering the harmful potential of pesticides, it is evident the importance of investigations regarding their commercialization for the identification of possible problems and planning of corrective actions.. In this context, the present research aimed to investigate variables related to the commercialization of pesticides in the municipality of Crisópolis-BA in the year 2021. Thus, information was collected from the establishments that sell pesticides in the municipality through observations and application of questionnaires to the owners and employees of the establishments. The data were analyzed using descriptive and inferential statistics. The results Showed a greater trend in sales for products with the active ingredient 2,4-D + picloram. These data a great demand and handling of these products by the population, which is a cause for concern considering their toxicological potential (toxicological class I). In addition, there was a preponderant lack of knowledge on the part of sellers about the safe use of pesticides. This is a worrisome fact, since the absence of information about its correct handling implies a greater risk of exposure, which may contribute to the intoxication of rural workers by these products.